Effect of different serotonin concentrations on the inotropic function and morphometric parameters of the heart of infant rats - Akhmetova, М.Zh. Akhmetova; Nigmatullina, R.R.; Tsyplakov, D.E.; Mindubayeva, F.А.; Tykezhanova, G.М. (Fundamental and Experimental Biology, 2022)
In recent years, studies of serotonin in physiological and pathological processes of the body have widely discussed its role as a link in the pathogenesis of atherosclerosis, arterial hypertension, and coronary heart disease. In the embryonic period, serotonin acts as a growth factor and plays an important regulatory role in the decisive period of embryo development, particularly, in the development of the heart. This research aims to study the influence of serotonin on the temporal parameters of contraction of the myocardium of the right ventricle in the newborn pups with a blockade of serotonin synthesis and membrane transporter in the embryonic period of ontogenesis. Thus, these studies have shown that the response of cardiomyocytes to serotonin is statistically higher in the group with excess serotonin and lower in the group with serotonin deficiency compared to the control group. The article also presents data indicating the change in serotonin concentration, which was created by the blockade of serotonin synthesis and the membrane transporter of serotonin in the embryonic period of ontogenesis, which results in morphological changes in the myocardium in early postnatal ontogenesis.